2015
DOI: 10.5194/amt-8-3617-2015
|View full text |Cite
|
Sign up to set email alerts
|

Mapping spectroscopic uncertainties into prospective methane retrieval errors from Sentinel-5 and its precursor

Abstract: Abstract. and its precursor (S5P) are future European satellite missions aiming at global monitoring of methane (CH 4 ) column-average dry air mole fractions (XCH 4 ). The spectrometers to be deployed onboard the satellites record spectra of sunlight backscattered from the Earth's surface and atmosphere. In particular, they exploit CH 4 absorption in the shortwave infrared spectral range around 1.65 µm (S5 only) and 2.35 µm (both S5 and S5P) wavelength. Given an accuracy goal of better than 2 % for XCH 4 to b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 46 publications
(49 reference statements)
2
15
0
Order By: Relevance
“…For now, however, we have found that adding the NIR band does not have added value for CH 4 retrievals. Furthermore, inaccuracies in current CH 4 and water vapor spectroscopic parameters could potentially introduce CH 4 retrieval errors as shown by Checa‐Garcia et al (), Frankenberg et al (), and Galli et al (). We see systematic spectral residuals that hint to such spectroscopic errors.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…For now, however, we have found that adding the NIR band does not have added value for CH 4 retrievals. Furthermore, inaccuracies in current CH 4 and water vapor spectroscopic parameters could potentially introduce CH 4 retrieval errors as shown by Checa‐Garcia et al (), Frankenberg et al (), and Galli et al (). We see systematic spectral residuals that hint to such spectroscopic errors.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Another relevant source of errors to the CH 4 data product could be spectroscopic errors. This has been studied in detail by Galli et al (2012) and Checa-Garcia et al (2015). Note that a study is ongoing to improve the spectroscopic data for TROPOMI's SWIR spectral range (Loos et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Such "physics-based" methods have been developed for space-based CO 2 and CH 4 measurements from SCIAMACHY, GOSAT and the Orbiting Carbon Observatory (OCO); see e.g. Connor et al (2008); Butz et al (2009) ;Reuter et al (2010); O'Dell et al (2012). The physics-based methods make use of the oxygen (O 2 ) A-band in the near-infrared (NIR) around 760 nm and absorption bands of the target absorber in the SWIR spectral range.…”
Section: Introductionmentioning
confidence: 99%